Manajemen Pengelolaan Pariwisata Ekslusif Berbasis Komponen 4A di Pulau Gili Iyang Kabupaten Sumenep - Ahmad Fauzi; Irwan Noor; Ainul Hayat; Muhammad Afnani Alifian (Universitas Darul Ulum, 2026)
Gili Iyang Island in Sumenep Regency, Madura, possesses the highest natural oxygen concentration in Indonesia and verified scientifically by LAPAN and BBTKLPP in 2006. This distinction positions Gili Iyang as a candidate for wellness tourism with a unique ecological comparative advantage. However, this extraordinary potential has not been accompanied by adequate tourism management. This study aims to describe and analyze the condition of exclusive tourism management based on the 4A components (Attraction, Accessibility, Amenities, Ancillary Services) in Gili Iyang, as well as to identify its supporting and inhibiting factors. A qualitative descriptive method was employed, with data collected through in-depth interviews, observation, and documentation. Results indicate that the Attraction component holds a unique ecological characteristic in the form of scientifically verified oxygen levels, yet remains unpackaged as a standardized wellness product. The Accessibility component still relies on irregular fishing boat transportation. The Amenities component provides only simple homestays without wellness facilities. The Ancillary Services component, including health, communication, and tour guide services, remains severely limited. The main supporting factor is the irreplaceable oxygen asset, involvement of Universitas Airlangga researchers, and the 2023 pier revitalization. The main inhibiting factors include inter-village conflicts of interest, limited regional fiscal capacity, and degradation trends in oxygen levels due to diesel emissions and motorized vehicle growth. This study recommends comprehensive and simultaneous 4A-based management as the policy foundation for exclusive wellness-based destination management.